Understanding primary prevention of cardiovascular disease. (2nd July 2021) - Bostock, Beverley
Abstract : Cardiovascular disease causes significant morbidity and mortality across the UK. Beverley Bostock looks at the role practice nurses can play in the primary prevention of this condition Nurses working in general practice play an important role in identifying those at risk of developing cardiovascular disease (CVD) and implementing person-focused risk reduction strategies. The NHS Health Check programme was designed to identify people between the age of 40 and 74 years with risk factors for CVD. Nurses in general practice have a key role to play in encouraging people to attend Health Checks and helping people to understand the potential benefits of CVD risk assessment and reduction strategies. Lifestyle interventions and pharmacological management allow modifiable risk factors to be managed in an evidence-based and person-focused way.